DoA-Based Microphone Array Position Self-Calibration Using Circular Statistic - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper we propose an approach to retrieve the absolute geometry of an acoustic sensor network, consisting of spatially distributed microphone arrays, from reverberant speech input. The calibration relies on direction of arrival measurements of the individual arrays. The proposed calibration algorithm is derived from a maximum-likelihood approach employing circular statistics. Since a sensor node consists of a microphone array with known intra-array geometry, we are able to obtain an absolute geometry estimate, including angles and distances. Simulation results demonstrate the effectiveness of the approach.
Keywords: Geometry calibration; microphone arrays; position self-calibration

Sampling Rate Synchronisation in Acoustic Sensor Networks with a Pre-Trained Clock Skew Error Model - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a combined hardware/software approach for synchronizing the sampling clocks of an acoustic sensor network. A first clock frequency offset estimate is obtained by a time stamp exchange protocol with a low data rate and computational requirements. The estimate is then postprocessed by a Kalman filter which exploits the specific properties of the statistics of the frequency offset estimation error. In long term experiments the deviation between the sampling oscillators of two sensor nodes never exceeded half a sample with a wired and with a wireless link between the nodes. The achieved precision enables the estimation of time difference of arrival values across different hardware devices without sharing a common sampling hardware.
Keywords: synchronization; acoustic sensor network

CuO and Co3O4 Nanoparticles: Synthesis, Characterizations, and Raman Spectroscopy - Rashad, M.; Rüsing, Michael; Berth, Gerhard; Lischka, K.; Pawlis, A. (Journal of Nanomaterials)
Copper oxide and cobalt oxide (CuO, Co3O4) nanocrystals (NCs) have been successfully prepared in a short time using microwave irradiation without any postannealing treatment. Both kinds of nanocrystals (NCs) have been prepared using copper nitrate and cobalt nitrate as the starting materials and distilled water as the solvent. The resulted powders of nanocrystals (NCs) were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) measurements. The obtained results confirm the presence of the both of oxides nanopowders produced during chemical precipitation using microwave irradiation. A strong emission under UV excitation is obtained from the prepared CuO and Co3O4 nanoparticles. The results show that the nanoparticles have high dispersion and narrow size distribution. The line scans of atomic force microscopy (AFM) images of the nanocrystals (NCs) sprayed on GaAs substrates confirm the results of both X-ray diffraction and transmission electron microscopy. Furthermore, vibrational studies have been carried out using Raman spectroscopic technique. Specific Raman peaks have been observed in the CuO and Co3O4 nanostructures, and the full width at half maximum (FWHM) of the peaks indicates a small particle size of the nanocrystals.
Keywords: General Materials Science

Server based indoor navigation using RSSI and inertial sensor information - Hoang, Manh Kha; Schmitz, Sarah; Drueke, Christian; Vu, Dang Hai Tran; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (Positioning Navigation and Communication (WPNC), 2013 10th Workshop on)
In this paper we present a system for indoor navigation based on received signal strength index information of Wireless-LAN access points and relative position estimates. The relative position information is gathered from inertial smartphone sensors using a step detection and an orientation estimate. Our map data is hosted on a server employing a map renderer and a SQL database. The database includes a complete multilevel office building, within which the user can navigate. During navigation, the client retrieves the position estimate from the server, together with the corresponding map tiles to visualize the user's position on the smartphone display.
Keywords: SQL; navigation; smart phones; wireless LAN; RSSI; SQL database; complete multilevel office building; inertial sensor information; inertial smartphone sensors; map renderer; received signal strength index information; relative position estimates; server based indoor navigation; step detection; wireless-LAN access points; Smartphone; fingerprint; indoor navigation; map tile

A Hidden Markov Model for Indoor User Tracking Based on WiFi Fingerprinting and Step Detection - Hoang, Manh Kha; Schmalenstroeer, Joerg; Drueke, Christian; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (21th European Signal Processing Conference (EUSIPCO 2013))
In this paper we present a modified hidden Markov model (HMM) for the fusion of received signal strength index (RSSI) information of WiFi access points and relative position information which is obtained from the inertial sensors of a smartphone for indoor positioning. Since the states of the HMM represent the potential user locations, their number determines the quantization error introduced by discretizing the allowable user positions through the use of the HMM. To reduce this quantization error we introduce â??pseudoâ?? states, whose emission probability, which models the RSSI measurements at this location, is synthesized from those of the neighboring states of which a Gaussian emission probability has been estimated during the training phase. The experimental results demonstrate the effectiveness of this approach. By introducing on average two pseudo states per original HMM state the positioning error could be significantly reduced without increasing the training effort.

Zeitgenössische Praktiken von Subjektivierung. Konsumismus, Kybernetischer Kapitalismus und Repräsentationskritik in Anschluss an Tiqquns Figur der Jungen-Mädchen - Degeling, Jasmin (onlinejournal kultur&geschlecht)

Rezension zu: Clemens Apprich / Felix Stalder (Hgg.): Vergessene Zukunft. Radikale Netzkulturen in Europa, Bielefeld: transcript 2012 - Schmitt, Martin (sehepunkte)

Scientiﬁc Literature Retrieval based on Terminological Paraphrases using Predicate Argument Tuple - Choi, Sung-Pil; Song, Sa-kwang; Jung, Hanmin; Geierhos, Michaela; Myaeng, Sung Hyon (Information Science and Industrial Applications: Proceedings, International Conference, ISI 2012, Cebu, Philippines, May 2012)
The conceptual condensability of technical terms permits us to use them as effective queries to search scientific databases. However, authors often employ alternative expressions to represent the meanings of specific terms, in other words, Terminological Paraphrases (TPs) in the literature for certain reasons. In this paper, we propose an effective way to retrieve “de facto relevance documents” which only contain those TPs and cannot be searched by conventional models in an environment with only controlled vocabularies by adapting Predicate Argument Tuple (PAT). The experiment confirms that PAT-based document retrieval is an effective and promising method to search those kinds of documents and to improve terminology-based scientific information access models.

A Proof-of-Concept of D³ Record Mining using Domain-Dependent Data - Lee, Yeong Su; Geierhos, Michaela; Song, Sa-Kwang; Jung, Hanmin (Software Technology: Prooceedings, International Conference, SoftTech 2012, Cebu, Philippines, May 2012)
Our purpose is to perform data record extraction from onlineevent calendars exploiting sublanguage and domain characteristics. We therefore use so-called domain-dependent data (D³) completely based on language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Moreover, another important criteria is that our system is robust to DOM and layout modifications made by web designers. Thus, preliminary experimental results are provided to demonstrate proof-of-concept of such an approach tested on websites in the German opera domain. Furthermore, we could show that our proposed technique outperforms other data record mining applications run on event sites.

Network Disruption and the Common Enemy Effect - Hoyer, Britta; De Jaegher, Kris
The phenomenon that groups or people work together when they face an opponent, although they have little in common otherwise, has been termed the "common enemy effect". We study a model of network formation, where players can use links to build a network, knowing that they are facing a common enemy who can disrupt the links within the network, and whose goal it is to minimize the sum of the benefits of the network. We find that introducing a common enemy can lead to the formation of stable and efficient networks as well as fragmented networks and the empty network.

Cloud Service Revenue Management - Püschel, Tim; Schryen, Guido; Hristova, Diana; Neumann, Dirk (European Conference on Information Systems)

Energy-Aware Workload Management Models for Operating Cost Reduction in Data Centers - Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (European Journal of Operational Research : EJOR)

Proof-Carrying Hardware: A Novel Approach to Reconfigurable Hardware Security - Drzevitzky, Stephanie
FPGAs, systems on chip and embedded systems are nowadays irreplaceable. They combine the computational power of application specific hardware with software-like flexibility. At runtime, they can adjust their functionality by downloading new hardware modules and integrating their functionality. Due to their growing capabilities, the demands made to reconfigurable hardware grow. Their deployment in increasingly security critical scenarios requires new ways of enforcing security since a failure in security has severe consequences. Aside from financial losses, a loss of human life and risks to national security are possible. With this work I present the novel and groundbreaking concept of proof-carrying hardware. It is a method for the verification of properties of hardware modules to guarantee security for a target platform at runtime. The producer of a hardware module delivers based on the consumer's safety policy a safety proof in combination with the reconfiguration bitstream. The extensive computation of a proof is a contrast to the comparatively undemanding checking of the proof. I present a prototype based on open-source tools and an abstract FPGA architecture and bitstream format. The proof of the usability of proof-carrying hardware provides the evaluation of the prototype with the exemplary application of securing combinational and bounded sequential equivalence of reference monitor modules for memory safety.

Dual-polarity plasmonic metalens for visible light - Chen, Xianzhong; Huang, Lingling; Mühlenbernd, Holger; Li, Guixin; Bai, Benfeng; Tan, Qiaofeng; Jin, Guofan; Qiu, Cheng-Wei; Zhang, Shuang; Zentgraf, Thomas (Nature Communications)

A Fuzzy Decision Support Model for Natural Disaster Response under Informational Uncertainty - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Operational Emergency Response under Informational Uncertainty: A Fuzzy Optimization Model for Scheduling and Allocating Rescue Units - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Conference on Information Systems for Crisis Response and Management (ISCRAM) 2012)

IS Design Thinking in Disaster Management Research - Schryen, Guido; Wex, Felix (45th Hawaii International Conference on System Sciences)

Profis im Netz: Soziale Netzwerke könnten in Unternehmen viel mehr Nutzen stiften - woran hakt es?, in: Die Zeit (12.04.2012) - Schryen, Guido (Die Zeit)

Soziale Netzwerke in Unternehmenskontexten - Potentiale und Anforderungen, in: Information Management & Consulting, to appear - Schryen, Guido (IM Information Management & Consulting)

Quality Analysis and Optimization of the MAP-based Noise Power Spectral Density Tracker - Chinaev, Aleksej; Haeb-Umbach, Reinhold (Speech Communication; 10. ITG Symposium; Proceedings.)